Aperiodic structures of rod-shaped precipitates in a Mg-Zn-Al alloy. (December 2021) - Zheng, Yunhe; Bourgeois, Laure; Nie, Jian-Feng
Abstract: Rod-shaped precipitates with their long axis parallel to [0001]α commonly form in Mg-Zn-Al alloys, providing strengthening effects. These precipitates are metastable and are generally accepted to be the MgZn2 and/or Mg4 Zn7 phases. In this paper, the cross-sectional structure of precipitate rods in an aged ZA84 alloy is examined at the atomic scale using high-angle annular dark-field scanning transmission electron microscopy. It is found that these precipitates are neither pure MgZn2 nor Mg4 Zn7 . The structures of the rod-shaped precipitates do not have long-range translational symmetry nor long-range 5-fold rotational symmetry in the two-dimensional projection plane perpendicular to the rod long axis. However, these structures can be described by the tiling of different shapes, with four such shapes being most frequently observed. The structural details revealed in this work may help rationalize the many complex precipitate structures in Mg-Zn-Al and Mg-Zn alloys. Graphical abstract: Image, graphical abstract